TBL1XR1 mutations in Pierpont syndrome are not restricted to the recurrent p.Tyr446Cys mutation. Issue 12 (26th October 2018) - Lemattre, C.; Thevenon, J.; Duffourd, Y.; Nambot, S.; Haquet, E.; Vuadelle, B.; Genevieve, D.; Sarda, P.; Bruel, A. L.; Kuentz, P.; Wells, C. F.; Faivre, L.; et al.
Abstract : Pierpont syndrome is a rare and sporadic syndrome, including developmental delay, facial characteristics, and abnormal extremities. Recently, a recurrent de novo TBL1XR1 variant (c.1337A > G; p.Tyr446Cys) has been identified in eight patients by whole‐exome sequencing. A dominant‐negative effect of this mutation is strongly suspected, since patients with TBL1XR1 deletion and other variants predicting loss of function do not share the same phenotype. We report two patients with typical Pierpont‐like syndrome features. Exome sequencing allowed identifying a de novo heterozygous missense TBL1XR1 variant in both patients, different from those already reported: p.Cys325Tyr and p.Tyr446His. The localization of these mutations and clinical features of Pierpont‐like syndrome suggest that their functional consequences are comparable with the recurrent mutation previously described, and provided additional data to understand molecular mechanisms of TBL1XR1 anomalies.